2009
DOI: 10.1189/jlb.1009673
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage polarization and HIV-1 infection

Abstract: Polarization of MP into classically activated (M1) and alternatively activated (M2a, M2b, and M2c) macrophages is critical in mediating an effective immune response against invading pathogens. However, several pathogens use these activation pathways to facilitate dissemination and pathogenesis. Viruses generally induce an M1-like phenotype during the acute phase of infection. In addition to promoting the development of Th1 responses and IFN production, M1 macrophages often produce cytokines that drive viral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
152
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 161 publications
(190 reference statements)
4
152
0
Order By: Relevance
“…The activation of MF by soluble HIV-1 proteins is thought to contribute to the sustained activation of the immune system observed in HIV-1 infection (6,17). Our finding that HIV-1 proteins, particularly Nef, preferentially target M2-MF, which predominate under normal conditions, and drive them toward MF with an M1-like phenotype provides a novel mechanism by which HIV-1 efficiently and rapidly induces the sustained immune activation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The activation of MF by soluble HIV-1 proteins is thought to contribute to the sustained activation of the immune system observed in HIV-1 infection (6,17). Our finding that HIV-1 proteins, particularly Nef, preferentially target M2-MF, which predominate under normal conditions, and drive them toward MF with an M1-like phenotype provides a novel mechanism by which HIV-1 efficiently and rapidly induces the sustained immune activation.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, it was suggested that, under normal conditions, peripheral blood monocytes are predisposed toward an M2 phenotype and are mostly devoted to tissue repair as a result of their stimulation by the relatively high levels of M-CSF present in sera (6,55). Indeed, a transcriptome analysis showed that M2 polarization involved a minimal alteration in MF steady-state mRNA expression compared with M1 polarization (14).…”
Section: Discussionmentioning
confidence: 99%
“…Various amounts of siRNAs were prediluted in 1 mL of Opti-MEM, to which 20 μL of INTERFERin was added, and the transfection mix was left at room temperature for 10 min. Transfection mix volumes of 32 μL, 125 μL, and 250 μL, respectively, were added to 6.5 × 10 4 , 2.5 × 10 5 , and 0.5 × 10 6 MDMs at final concentrations of 50 nM sip21, siRNR2, or siE2F1 siRNAs, and 25 nM siRB1 siRNAs. Equal amounts of on-target plus nontargeting siRNAs were added to control MDMs.…”
Section: Methodsmentioning
confidence: 99%
“…HIV-1 infection of macrophages also affects their functions in innate and adaptive responses to pathogens (5). However, macrophage susceptibility to HIV-1 infection varies according to their differentiation status and tissue localization (6,7). Environmental stimuli such as cytokines, bacterial products, and immune complexes also influence macrophage permissiveness to HIV-1 infection (8).…”
mentioning
confidence: 99%
“…By analogy to Th1/Th2 polarization observed in T cells, macrophages can also undergo functional polarization in response to microbial products and host cytokines (68). These polarization pathways have been designated M1 and M2 (69) in which M1 or classically activated macrophages are highly microbicidal, secrete proinflammatory mediators such as TNF, IL-1, IL-12, and IL-6, and are important producers of reactive nitrogen and oxygen intermediates, whereas M2 or alternatively activated macrophages are involved in the resolution of inflammation and tissue repair and secrete anti-inflammatory mediators such as IL-10 (70).…”
Section: Hiv-1-mediated Baff Induction Is Modulated By the Macrophagementioning
confidence: 99%